Financial literacy and sustainability of rural microfinance: The mediating effect of governance - Apriani Dorkas Rambu Atahau; Imanuel Madea Sakti; Alliny Namilana Rambu Hutar; Andrian Dolfriandra Huruta; Min-Sun Kim (Cogent Economics & Finance, 2023)
This research aims to examine the mediating role of microfinance governance in the relationship between financial literacy and microfinance sustainability. The research used the purposive sampling method to collect data from the Women Farmers Group (WFG) "Tapa Walla Badi" in Mbatakapidu village, East Sumba, Indonesia. The survey was conducted from November through December 2021 with the valid sample for analysis was 200 questionnaires. The Partial Least Squares-Structural Equation Model (PLS-SEM) was used for analysis. The bootstrapping and the Sobel test were required for a better understanding of the findings. Robust test and focus group discussion (FGD) made our methodology more reliable. The findings show that financial literacy plays an important role in the transformation of rural microfinance institutions (MFIs). Financial literacy works positively on the sustainability of rural microfinance via governance. Age, gender, education, and employment situation were taken into account in financial literacy. This research provides a comprehensive view to policymakers in developing rural MFIs, thus implies the urgency to promote financial literacy and improve governance structures within MFIs. The local government may create pro-financial inclusion policies that support sustainable MFIs by implementing financial literacy curriculum in formal and non-formal education.
Keywords: G21; G30; G53; 330; financial literacy; financial literacy index; governance; microfinance sustainability; rural microfinance institutions